The content of future lecturer psychology-pedagogical preparation to professional creative activity (Pedagogy of Higher and Secondary Education, 2013)
Sgadova V. V. The content of future lecturer psychology-pedagogical preparation to professional creative activity.The content of psychology-pedagogical preparation of future lecturers to professional creative activity is analyzed. Different forms of students’ educational activity which develop their creative skills are highlighted.
Keywords: methodological; theoretical; methodical and technoldge; creative skills; conditions providing psychology-pedagogical preparation of students to professional creative activity